2011
DOI: 10.1111/j.1365-2214.2011.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life of children with cerebral palsy: a systematic review of clinical trials

Abstract: Current review suggests that positive effect was shown in medicinal and motor control interventions on QoL. However, no single interventional approach can demonstrate a consistent positive impact on QoL across different studies. Future studies are recommended to (i) provide a clear definition of QoL, and investigate the relationship between symptoms' severity and QoL; (ii) measure outcome at different time points to capture real effects of interventions; and (iii) make more use of valid outcome instruments, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
0
31
0
3
Order By: Relevance
“…Prior research has found a strong correlation with physical QOL but the association with psychosocial QOL is less clear [7, 1315]. Given this, we hypothesize that patient psychosocial QOL will not be associated with severity and comorbidity; (2) to determine if there is an association between the receipt of family centered care and psychosocial QOL for these children.…”
Section: Introductionmentioning
confidence: 95%
“…Prior research has found a strong correlation with physical QOL but the association with psychosocial QOL is less clear [7, 1315]. Given this, we hypothesize that patient psychosocial QOL will not be associated with severity and comorbidity; (2) to determine if there is an association between the receipt of family centered care and psychosocial QOL for these children.…”
Section: Introductionmentioning
confidence: 95%
“…Although QoL is considered to be a multidimensional construct, there is no consensus regarding the relevant domains or the content of the QoL domains (Tsoi et al . ). In their review, Albers et al .…”
Section: Discussionmentioning
confidence: 97%
“…found some positive effect of certain medicinal and motor control interventions on QoL in children with cerebral palsy ( n = 347, average age 9.1 years) (Tsoi et al . ). In their study on pain, motor function and health‐related QoL in children ( n = 91, age 8–19 years, GMFCS level IV‐V 51.6%, severe cognitive impairment 30.8%), Badia et al .…”
Section: Introductionmentioning
confidence: 97%
“…Significant effects of ITB therapy on severe spasticity have subsequently been confirmed, as has maintenance of this effect during long-term administration. 2,4,19,22,27,28) In 2005, this procedure was finally approved in Japan, clinical use has been permitted since 2006, and reports of efficacy are now appearing in Japan. ITB therapy is a non-destructive treatment that is administered from an implantable pump under the control of a programmer, offering an outstanding treatment method that provides both variability and adjustability.…”
Section: Introductionmentioning
confidence: 99%